2017
DOI: 10.29252/ijn.30.109.67
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Self-esteem between Burnout and Social Undermining in the Nurses of Charity Hospitals in Mashhad

Abstract: Background & Aim: communication with the board of nursing as well as patient and their families are one of the most important daily activities of nurses. On one hand, Nurses are in close contact with people and are responsible for their health and life, and on the other hand, burnout influences the quality of patient care. Therefore, the identification of factors affecting the burnout of nurses and the variables involved in this effect will be helpful in improving the quality of health services. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The study results showed that social undermining perceived by deluxe hotel employees positively influenced their emotional exhaustion. This is consistent with previous studies that showed that employees' emotional exhaustion became severe when they experienced social undermining in a job situation [30,31,34]. In addition, when emotional exhaustion became severe, employees' procrastination behavior that was harmful to their organizations increased; this suggested that the emotional exhaustion they experience in their organizations is likely to lead to a high level of procrastination behavior [53].…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 90%
See 2 more Smart Citations
“…The study results showed that social undermining perceived by deluxe hotel employees positively influenced their emotional exhaustion. This is consistent with previous studies that showed that employees' emotional exhaustion became severe when they experienced social undermining in a job situation [30,31,34]. In addition, when emotional exhaustion became severe, employees' procrastination behavior that was harmful to their organizations increased; this suggested that the emotional exhaustion they experience in their organizations is likely to lead to a high level of procrastination behavior [53].…”
Section: Discussion and Theoretical Implicationssupporting
confidence: 90%
“…In addition, Strongman [33] found that social undermining aggravated individuals' psychological pain and emotional exhaustion, whereas social support increased their emotional health. Rahimnia et al [34] determined that social undermining experienced by nurses in their work environment increased their burnout and that decreasing the elements of social undermining may weaken their burnout. Furthermore, Sârbescu et al [2] asserted that social undermining committed by supervisors increased employees' burnout and that their experience of social undermining was closely related with their emotional exhaustion [35].…”
Section: Relationships Among Social Undermining and Emotional Exhaustionmentioning
confidence: 99%
See 1 more Smart Citation